Melatonin alleviates PM2.5‐induced glucose metabolism disorder and lipidome alteration by regulating endoplasmic reticulum stress. Issue 4 (29th August 2022) - Du, Zhou; Hu, Junjie; Lin, Lisen; Liang, Qingqing; Sun, Mengqi; Sun, Zhiwei; Duan, Junchao
Abstract: Exposure to fine particulate matter (PM2.5 ) was associated with an increased incidence of liver metabolic disease. Melatonin has been shown to prevent liver glucolipid metabolism disorders. However, whether melatonin could rescue PM2.5 ‐induced liver metabolic abnormalities remains uncertain. This study was to evaluate the mitigating effect of melatonin on PM2.5 ‐accelerated hepatic glucose metabolism imbalance in vivo and in vitro. Schiff periodic acid shiff staining and other results showed that PM2.5 led to a decrease in hepatic glycogen reserve and an increase in glucose content, which was effectively alleviated by melatonin. Targeted lipidomics is used to identify lipid biomarkers associated with this process, including glycerolipids, glycerophospholipids, and sphingolipids. In addition, gene microarray and quantitative polymerase chain reaction analysis of ApoE −/− mice liver suggested that PM2.5 activated the miR‐200a‐3p and inhibited DNAJB9, and the targeting relationship was verified by luciferase reports for the first time. Further investigation demonstrated that DNAJB9 might motivate endoplasmic reticulum (ER) stress by regulating Ca 2+ homeostasis, thus altering the protein expression of GSK3B, FOXO1, and PCK2. Meanwhile, melatonin effectively inhibited miR‐200a‐3p and glucose metabolism disorder. Knockout of miR‐200a‐3p in L02 cells revealed that miR‐200a‐3p is indispensable in the damage of PM2.5 and the therapeutic effect of melatonin. In summary, melatonin alleviated PM2.5 ‐induced liver metabolic dysregulation by regulating ER stress via miR‐200a‐3p/DNAJB9 signaling pathway. Our data provide a prospective targeted therapy for air pollution‐related liver metabolism disorders.